World's funniest commercials - Karrin, Bonnie; Sullivan, Damian; DeMoraes, Ron (Stamford, CT : ABC Video, 2002)
This TV program presents a collection of international humorous commercials
Executive producer, Woody Fraser
Host: Leslie Nielson
VCD format
Keywords: Comedy films